Developing a real time digital emergency personal safety app to assist in emergency situation using best time - Ong, Jun Kai (2019)

(untitled)
People nowadays are concerning about their personal safety issues which will often be threatened. It is important to develop a real time digital emergency personal safety app to assist in emergency situations using best time. This mobile application is called “One Tap” emergency personal safety app which is mainly designed in android-based operating system and target on android version 5.0 or above. One Tap provides a lot of features that can assist in emergency situation such as sending an emergency message to the selected contacts by pressing a button. The emergency message contained personal information such as name, home address and current location will send to the particular contacts. Besides, this application has designed a widget button that display in the device’s home page where it can be accessed quickly without launching the app. There is also a feature that tracking the location of nearby hospital, pharmacy and police station in the map displayed. Some of the users may unfamiliar with the places, hence they can find the nearby hospital, pharmacy and police station easily in the case of emergency. In order to provide additional information of the accident happened, the eyewitnesses or the users can capture the photo and share in the app where all the users can view and assist the victim if they are around the places. Towards the end, the people who received the help request can response to the accident within best time, and finally rescue them in an effective and efficient ways. Therefore by using this app, people are able to manage their personal safety and reduce the risk of death when they are involved in an accident.